2009
DOI: 10.1007/s11999-009-0824-8
|View full text |Cite
|
Sign up to set email alerts
|

Periacetabular Osteotomy for Acetabular Dysplasia in Patients Older than 40 Years: A Preliminary Study

Abstract: The functional outcomes of periacetabular osteotomy (PAO) and factors predicting outcome in the older patient with acetabular dysplasia are not well understood. We therefore retrospectively determined the functional outcome of 70 patients (87 hips) over age 40 treated with PAO in three institutions; we also determined whether preoperative factors, particularly the presence of osteoarthritis, influenced the survival of the hip or time to total hip arthroplasty after PAO. The average age at surgery was 43.6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 21 publications
7
57
1
Order By: Relevance
“…The musculature on the outer wall of the pelvis is now routinely preserved leaving the tensor fascia lata and gluteus medius intact [12]. The operation is also easily executed without detaching the rectus femoris, further minimizing injury to the soft tissue during dissection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The musculature on the outer wall of the pelvis is now routinely preserved leaving the tensor fascia lata and gluteus medius intact [12]. The operation is also easily executed without detaching the rectus femoris, further minimizing injury to the soft tissue during dissection.…”
mentioning
confidence: 99%
“…Several studies have suggested that age greater than 35-40 years is a negative prognostic indicator [12,20,21]. However, others have reported good results in patients as old as 55 years [22].…”
mentioning
confidence: 99%
“…With regard to age at the time of surgery, several authors suggest the indication for osteotomy in older patients should be restricted to those with pre-or early-stage OA [31,65], with unilateral involvement [61], or with postoperative good joint congruency expected [31,65]. Failure of these procedures with conversion to THA occurred in 0% to 17% of the cases in PAO at mean followup times ranging from 3 to 7 years [5] and in 0% to 10% in RAO at followup times ranging from 7 [53] to 10 years [41] (Table 2).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Millis et al and Garbuz et al both reported good outcome of PAO in patients over the age of 40 [2,9]. Millis et al also published a survival rate of 76 % after average 4.9 years follow-up [2].…”
Section: Introductionmentioning
confidence: 95%
“…As one of the joint preserving operations, PAO is usually suggested for the treatment of developmental dysplasia of hip (DDH) in adolescents and young adults. Old people with severe osteoarthritis are more suitable for hip replacement, since older age and higher preoperative osteoarthritis grade have been identified as two important predictors of PAO failure [1][2][3][4][5]. Debate has focussed on the treatment of middle aged DDH patients who usually have mild or moderate osteoarthritis at an age of 35-54 years, especially when the reported survival rate of hip prosthesis is much greater than it used to be [6,7].…”
Section: Introductionmentioning
confidence: 99%